EFFECTIVENESS AND CONTRIBUTION OF LOCAL TAXES AGAINST LOCAL NATIVE INCOME OF TERNATE - Zulkhaira, Ismiyati; Zainudin; Djaelani, Yustiana; Jeandry, Gregorius (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
Tax is one of the sources of revenue and financing of a country's activities. Tax has a great contribution for developing of country. This study aims to determine how effective tax revenue and local tax contributions are to the PAD of Ternate City in 2018-2022 (5 years). The data was obtained from the Regional Revenue and Retribution. The analysis technique employed in this study is descriptive analysis, which aims to systematically describe and summarize the effectiveness of Local Revenue (Pendapatan Asli Daerah, PAD). This approach focuses on presenting the data as it is, without attempting to draw general conclusions or infer relationships between variables The results of data analysis shows that the effectiveness of regional taxes reaches 105%, so it is categorized as very effective. Local tax contributions in Ternate City in 2018-2022 are 70%, 71%, 69%, 71%, 73%. The average Ternate City Regional Tax Controversy reaches 71% so that it can be categorized well.